2009
DOI: 10.1074/mcp.m800206-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of the Excretory/Secretory Component of the Blood-feeding Stage of the Hookworm, Ancylostoma caninum

Abstract: Hookworms are blood-feeding intestinal parasites of mammalian hosts and are one of the major human ailments affecting ϳ600 million people worldwide. These parasites form an intimate association with the host and are able to avoid vigorous immune responses in many ways including skewing of the response phenotype to promote parasite survival and longevity. The primary interface between the parasite and the host is the excretory/secretory component, a complex mixture of proteins, carbohydrates, and lipids secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(180 citation statements)
references
References 63 publications
12
168
0
Order By: Relevance
“…In particular, a significant proportion of nonclassically secreted ES proteins, including a number of proteins predicted to be membrane bound, such as a tetraspanin and a glucose transporter, were identified. Unlike ES products from gastrointestinal parasitic nematodes, such as Ancylostoma caninum (31), in which classically secreted proteins are very abundant, nonclassically secreted proteins have been consistently shown to represent a significant proportion of ES products from trematode parasites, including S. japonicum (79), C. sinensis (67), O. viverrini (68), and Fa. hepatica (66).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a significant proportion of nonclassically secreted ES proteins, including a number of proteins predicted to be membrane bound, such as a tetraspanin and a glucose transporter, were identified. Unlike ES products from gastrointestinal parasitic nematodes, such as Ancylostoma caninum (31), in which classically secreted proteins are very abundant, nonclassically secreted proteins have been consistently shown to represent a significant proportion of ES products from trematode parasites, including S. japonicum (79), C. sinensis (67), O. viverrini (68), and Fa. hepatica (66).…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter was repeatedly detected in the various ESPs from different parasites, including Ancylostoma caninum (25), Teladorsagia circumcincta (26), and S. mansoni (35), suggesting that such proteins are purposely released by parasites through an unknown excretory mechanism. Some ES proteins were predicted as non-secreted possibly due to N-terminal sequence truncations, which are common in EST clusters assembled with 3Ј-mRNA-enriched ESTs (41,42).…”
Section: Fig 1 Extraction Of Es Proteins Of Adult Worms Of S Japonmentioning
confidence: 99%
“…Importantly this information can be expected to facilitate the discovery of vaccines and new therapeutic drug targets as well as new diagnostic reagents for schistosomiasis control. Proteomics approaches encompass the most efficient and powerful tools for identification of protein complexes and have been widely used to decipher the ES components of the filarial parasite Brugia malayi (19), Leishmania (Trypanosomatidae) (20), nematodes (21)(22)(23)(24)(25)(26), and Trematoda (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). For the genus Schistosoma, the ES compositions of S. mansoni have been identified in many developmental life stages, including sporocyst (34), cercaria (35,36), and egg (37) but have not been characterized in the adult worm.…”
mentioning
confidence: 99%
“…Such efforts require an improved knowledge of hookworm disease on the molecular and immunological levels, and, more specifically, the pathogen-host interactions. In this context, previous studies have suggested a prominent role for activation-associated proteins (ASPs) which are amongst the ten most abundant groups of proteins in hookworms (Cantacessi et al, 2009) and the major constituents of the excretory/secretory (ES) proteins released by the blood-feeding adult stage hookworms (Mulvenna et al, 2009). ASPs belong to a large group of proteins called the 'sperm-coating protein (SCP)-like extracellular proteins', also known as SCP/Tpx-1/Ag5/PR-1/Sc7 (SCP/TAPS; Pfam accession no PF00188).…”
Section: Introductionmentioning
confidence: 99%